Scaling analysis of the Telegram Open Network blockchain project - Yukhymenko, V.I.; Fediushyn, O.I. (Radiotekhnika, 2022)
Blockchain systems are always distributed but differ greatly in resolutions, sizes, roles, transparency, types of participants, and the way transactions are handled. The decentralized structure offers inalienable security benefits, but with a large number of participants faces the problem of limited scaling. Sharding is suggested to solve this problem. Sharding is a way to divide consensual workload and transactions into several nodes. Effective application of sharding requires a lot of detail and work in terms of architecture and system implementation. As was found in the process of the work, in order to achieve significant results in scaling the blockchain system through sharding, it is necessary that the blockchain project is based on several blockchains simultaneously (i.e. had a multi-blockchain architecture) and provides infrastructure for fast and reliable messaging between them (i.e. strongly interconnected). The Telegram Open Network (TON) and its component TON Blockchain are considered an example of such a project. This work provides a comparative analysis of the most popular blockchain platforms (Bitcoin and Ethereum) with the implementations of TON Blockchain ideas (The Open Network and Everscale) on three parameters: system bandwidth (measured at transactions per second, abbreviated TPS), the average time of a new block’s appearance in the network and projected bandwidth in TPS.